2015
DOI: 10.1080/00405000.2015.1018669
|View full text |Cite
|
Sign up to set email alerts
|

Dyeing process parameters optimisation and colour strength prediction for viscose/lycra blended knitted fabrics using Taguchi method

Abstract: The main purpose of this study was to find the optimal dyeing conditions as well as predict the colour strength (CS) of viscose/lycra blended knitted fabrics using Taguchi method. The controllable factors such as dye concentration, temperature, time, alkali concentration, salt concentration and liquor ratio have been used as input variables and CS of the fabric as response variable for the construction of Taguchi model. An L 25 orthogonal array design has been chosen and conducted 25 experiments with three run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…Upon dyeing through firm covalent bonding, the dyed fabric resists in fading the color. The conjugation system, in the dye molecule and benzenoid structure present in Reactive Violet H3R dye using play their role when the fabrics are exposed to heat, light, and detergents, which in turn helps to improve the grading upon comparison at greyscale [34,35]. Hence it is concluded that U.S. treatment has improved the rating of colorfastness properties of cellulosic fabric when treated for 30 min.…”
Section: Resultsmentioning
confidence: 97%
“…Upon dyeing through firm covalent bonding, the dyed fabric resists in fading the color. The conjugation system, in the dye molecule and benzenoid structure present in Reactive Violet H3R dye using play their role when the fabrics are exposed to heat, light, and detergents, which in turn helps to improve the grading upon comparison at greyscale [34,35]. Hence it is concluded that U.S. treatment has improved the rating of colorfastness properties of cellulosic fabric when treated for 30 min.…”
Section: Resultsmentioning
confidence: 97%
“…The knitted textile materials produced from cellulosic viscose and cotton fiber fabrics are very popular for apparel wear due to their unique properties such as wear comfort, excellent hydrophilicity, biodegradability, air permeability, soft to the skin, superior moisture absorbent, easy-care properties and good capacity to pick up various classes of dyestuffs over woven fabrics, [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. A linear polymer cellulose encompass the repeating unit D-anhydroglucose joined together by β (1–4) glycosidic linkages.…”
Section: Introductionmentioning
confidence: 99%
“…The color strength, color fastness and pilling resistance are the fundamental quality characteristics of the dyed fabrics to the consumers. However, in the textile dyeing industry, color strength/color shade variance and poor color fastness properties in dyed fabrics are some of the most important reasons for fabric refusal [ 2 , 3 , 4 , 9 , 10 , 11 , 12 ]. Likewise, the pilling of knitted fabric is an undesirable property that affects the handle and appearance drastically and declines the service life of the products [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Color strength and fastness were used as the characteristic values for Taguchi analysis. However, the Taguchi method is primarily suited for single characteristic value problems and does not easily handle multiple characteristic values [7][8][9][10][11]. To solve this multiple-characteristic value problem, two methods were implemented in this study-single characteristic value conversion and minimummaximum selection method.…”
Section: Introductionmentioning
confidence: 99%